The European Second Generation Compared : Does the Integration Context Matter? - Lelie, Frans; Crul, Maurice; Schneider, Jens; Lelie, Frans; Crul, Maurice; Schneider, Jens (Amsterdam University Press, 2012)
Integration of newcomers is a foremost challenge for contemporary Europe. The 'second generation' - children born of immigrant parentage - is crucial in this process, for they constitute a growing and increasingly vocal segment of the metropolitan youth. This book offers an unprecedented look at the real-life place and position of the European second generation in education, labour, social relations, religion and identity formation. Using data collected by the TIES survey in fifteen cities across eight European countries, the authors paint a vivid picture of how the children of immigrants from Turkey, Morocco and former Yugoslavia are progressing. Their findings and cross-national comparisons are demographically compelling and at times revelational.
De kinderen van nieuwkomers in Europa vormen een snel groeiende en vaak opvallende groep jongeren, maar toch is er nauwelijks vergelijkend onderzoek naar gedaan. Voor dit boek werd op grote schaal informatie verzameld op het gebied van onderwijs, werk, sociale relaties, religie en identiteitsvorming. Daardoor ontstaat een helder beeld van de positie van de kinderen van immigranten uit Turkije, Marokko en voormalig Joegoslavië in 15 Europese steden. Een vergelijking tussen deze steden biedt daarbij inzicht in de sterke en zwakke punten van sociaal en integratiebeleid.
English
Keywords: Sociology & anthropology; sociology; sociologie; Austria; Belgium; Brussels; France; Germany; Labour economics; Netherlands; Stockholm; Sweden; Switzerland